Translanguaging under platform capitalism: multilingual identity performances among Indonesian content creators on Youtube - Cindy Eka Aulia (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s expanding creator economy has transformed YouTube into a commercial arena where multilingual resources mediate communication, identity, visibility, and cultural value across local, national, and transnational audiences. Objective: This study investigates how Indonesian content creators deploy translanguaging to perform multilingual identities while negotiating observable logics of platform capitalism. Method: Using a qualitative digital discourse design, this study integrates translanguaging moment analysis, multimodal discourse analysis, and critical platform analysis across creator videos, transcripts, visual frames, audience responses, platform policies, and publicly visible commercial cues. Results: Findings indicate that lexical insertion, intrasentential movement, regional stylisation, humour, clarification, and audience accommodation constitute prominent communicative resources within Indonesian-dominant discourse. Glocal, cosmopolitan, regional, professional, national, and authentic identities emerge through coordinated relations among language choice, vocal delivery, setting, gesture, editing, subtitles, visual composition, and cultural symbolism. Implication: Multilingual practices also intersect with discoverability framing, engagement prompts, sponsorship integration, audience segmentation, membership promotion, and branded self-presentation, although this study does not infer direct algorithmic causation from these observable correspondences. Novelty: This study contributes a platform-sensitive account of translanguaging by conceptualising multilingual performance as identity labour situated between expressive agency, audience accessibility, cultural authenticity, commercial differentiation, and infrastructural demands for visibility within Indonesia’s increasingly metrics-driven digital cultural economy.